2010
DOI: 10.2215/cjn.00950110
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor-23 and Parathyroid Hormone Are Associated with Post-Transplant Bone Mineral Density Loss

Abstract: Background and objectives: Among the multiple factors contributing to bone mineral density (BMD) loss after renal transplantation, hypophosphatemia is increasingly recognized to play an important role. Hypophosphatemia occurs in up to 90% of the renal transplant recipients in the early post-transplant period and is caused by renal phosphate wasting. We hypothesized that a high pretransplant level of the recently described phosphaturic hormone fibroblast growth factor 23 (FGF-23) is a risk factor for accelerate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 31 publications
2
15
0
2
Order By: Relevance
“…We have no bone biopsies to confirm the diagnosis, and thus, no definite conclusions can be drawn from this observation. Evenepoel et al [18] showed that low levels of iPTH and high levels of fibroblast growth factor 23 are associated with post-transplant bone mineral density loss [23] which suggests a higher risk of fractures for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…We have no bone biopsies to confirm the diagnosis, and thus, no definite conclusions can be drawn from this observation. Evenepoel et al [18] showed that low levels of iPTH and high levels of fibroblast growth factor 23 are associated with post-transplant bone mineral density loss [23] which suggests a higher risk of fractures for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…The relationships between FGF-23/ Klotho levels and bone mineral density (BMD) have been analysed in several studies, but fi ndings show either a weak relationship with BMD [23,24] or no relationship at all [25]. On the contrary, several studies have reported close relationships between FGF-23 and vascular risk, as commented later.…”
Section: Fgf-23-α Klotho Axismentioning
confidence: 99%
“…Kanaan and associates performed a two-center observational retrospective cohort study in 127 renal transplant recipients and found that patients with high serum FGF23 levels and/or low PTH levels at time of transplant are at risk for increased BMD loss during the first year posttransplant. 47 Fernandez and associates explored circulating FGF23 in association with fatness and insulin sensitivity, atherosclerosis, and BMD in 2 cohort studies and concluded that the associations between circulating FGF23 concentrations and glucose metabolism, BMD, and atherosclerosis are dependent on iron and obesity status-associated insulin resistance. 48 Fibroblast growth factor 23 and allograft outcomes Allograft and patient survival rates have improved steadily over the past decades as a result of advances in surgical techniques, immunosuppressive regimens, and prophylaxis against opportunistic infections.…”
Section: Bone Mineral Loss After Renal Transplantmentioning
confidence: 99%